Study of Icthyofaunal Biodiversity and Limnological Parameter in Kelo Dam of Raigarh, District – Raigarh C.G. - Jaiswal, Peeyoosh Tiwari; Jaiswal , Prakash Kumar; Sahu , K. R.; Pandey, Pratibha (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The Kelo River is the lifeline of Raigarh. It originates from a place called Ludeg of Gharghoda Its total length is about 90 kilometers. At a distance of 8 kilometers from Raigarh district on Raigarh Ambikapur state highway road, Kelo dam was constructed on this River in The Danout Village. It’s also Known as ̔ Late Dilip Singh Judeo project. Limnolgical properties of Kelo dam water were tested as per Method Given by APHA 2005 which shown seasonal variation. The Current study on Kelo dam was carried out from. March 2021 to February 2022. At the time of study the species of fishes were collected by different fish nets with the help of local fisherman. The collected fish were photographed and preserved in 10% formalin solution. The collected fishes were identified with the help of standard books of Jayaram, K.C. [1], Francis Day, [2], and Shrivastava, G. [3]. During the entire study period a total of 22 fish species were recorded from this study, it was found that most of the water parameter were under permissible limit and Kelo dam water quality is suitable for biodiversity and irrigation.